2011
DOI: 10.1007/bf03356377
|View full text |Cite
|
Sign up to set email alerts
|

Toxic and behavioural effects of carvacrol and thymol on Frankliniella occidentalis larvae

Abstract: Bioassays using bean leaf discs were conducted to investigate toxic and behaviour-modifying effects of carvacrol and thymol, two monoterpenoid phenols, on second instar larvae of Frankliniella occidentalis (Thysanoptera: Thripidae) at concentrations of 0.1% and 1%. We tested the contact toxicity of carvacrol and thymol to F. occidentalis larvae and studied the settlement preference of thrips larvae for treated or untreated bean leaf discs and the effects of the compounds on their feeding activity. Mortality ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Applications of methyl‐jasmonate and cis‐jasmone deterred WFT larvae from feeding and settling, although repeated exposure resulted in a dose‐dependent habituation . The monoterpenoid phenols thymol and carvacrol exhibited both a feeding as well as a oviposition deterrent effect to WFT …”
Section: Wft Control Tacticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of methyl‐jasmonate and cis‐jasmone deterred WFT larvae from feeding and settling, although repeated exposure resulted in a dose‐dependent habituation . The monoterpenoid phenols thymol and carvacrol exhibited both a feeding as well as a oviposition deterrent effect to WFT …”
Section: Wft Control Tacticsmentioning
confidence: 99%
“…93,94 The monoterpenoid phenols thymol and carvacrol exhibited both a feeding as well as a oviposition deterrent effect to WFT. 95,96 Currently, the three commercially available WFT semiochemicals are mainly used as lures in conjunction with sticky card traps. Adult thrips constantly explore their host range for feeding and reproduction by utilising different cues, including volatiles.…”
Section: Allelochemicalsmentioning
confidence: 99%
“…Numerous studies have demonstrated that exogenous biotic and abiotic elicitors have been used to induce host plant defense against F. occidentalis , for example, Pseudomonas syringae , coronatine [ 10 ], jasmonic acid (JA) [ 3 , 35 ], salicylic acid (SA) [ 36 ], ultraviolet [ 37 ], light intensity [ 38 ], nitrogen fertilizer [ 39 ], CO 2 [ 40 ], secondary substances (α-ionone, eugenol, thymol, carvacrol and alkaloids, etc.) [ 41 , 42 ], and protein inhibitors [ 43 ]. In the present study, Ca treatment on kidney bean plants also influenced the population parameters and preference of F. occidentalis .…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, only one study with antifeedants was carried out with thrips larvae so far: carvacrol and thymol, two monoterpenoid phenols, applied to the test plants at a concentration of 1 % deterred F. occidentalis second instar larvae in choice bioassays. In addition, the feeding damage of the larvae was reduced in a no-choice situation (Peneder and Koschier 2011 ).…”
Section: Discussionmentioning
confidence: 99%